Clusterin ameliorates tau pathology in vivo by inhibiting fibril formation - Wojtas, Aleksandra M. (Acta Neuropathol Commun, 2020)
The molecular chaperone Clusterin (CLU) impacts the amyloid pathway in Alzheimer’s disease (AD) but its role in tau pathology is unknown. We observed CLU co-localization with tau aggregates in AD and primary tauopathies and CLU levels were upregulated in response to tau accumulation. To further elucidate the effect of CLU on tau pathology, we utilized a gene delivery approach in CLU knock-out (CLU KO) mice to drive expression of tau bearing the P301L mutation. We found that loss of CLU was associated with exacerbated tau pathology and anxiety-like behaviors in our mouse model of tauopathy. Additionally, we found that CLU dramatically inhibited tau fibrilization using an in vitro assay. Together, these results demonstrate that CLU plays a major role in both amyloid and tau pathologies in AD. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40478-020-01079-1) contains supplementary material, which is available to authorized users.